Role and therapeutic potential of dietary ketone bodies in lymph vessel growth - García-Caballero, Melissa (My University, 2021)
Lymphatic vessels (LVs), lined by lymphatic endothelial cells (LECs), are indispensable for life. However, the role of metabolism in LECs has been incompletely elucidated. In our study, it is reported that LEC-specific loss of OXCT1, a key enzyme of ketone body oxidation, reduces LEC proliferation, migration and vessel sprouting in vitro and impairs lymphangiogenesis in development and disease in Prox1ΔOXCT1 mice. Mechanistically, OXCT1 silencing lowers acetyl-CoA levels, tricarboxylic acid cycle metabolite pools, and nucleotide precursor and deoxynucleotide triphosphate levels required for LEC proliferation. Ketone body supplementation to LECs induces the opposite effects. Notably, elevation of lymph ketone body levels by a high-fat, low-carbohydrate ketogenic diet or by administration of the ketone body β-hydroxybutyrate increases lymphangiogenesis after corneal injury and myocardial infarction. Intriguingly, in a mouse model of microsurgical ablation of LVs in the tail, which repeats features of acquired lymphedema in humans, the ketogenic diet improves LV function and growth, reduces infiltration of anti-lymphangiogenic immune cells and decreases edema, suggesting a novel dietary therapeutic opportunity.
LERN, NAVBO
Keywords: Metabolismo; Vasos linfáticos; Metabolism; Lymphatic vessels; Lymphedema